Kajian Dampak Program Kampung Keluarga Berkualitas terhadap Percepatan Penurunan Stunting di Kabupaten Sleman: The Impact of the Family Quality Village Program on Accelerating Stunting Reduction Efforts in Sleman Regency - Lestari, Lily Arsanti; Helmyati, Siti; Kusuma, Mutiara Tirta Prabandari Lintang; Rachmawati, Yuliana Novita; Suryani, Ita (Amerta Nutrition, 2024)
Background: Stunting is a significant nutrition problem in Indonesia. The current national prevalence is 21.6%, whereas the prevalence in the Yogyakarta Province and Sleman Regency are 16.4% and 15%, respectively. The Family Quality Village Program is initiated to accelerate stunting reduction efforts by empowering families in health, education, and entrepreneurship. Objectives: This study evaluated the implementation and impact of the Family Quality Village Program in Sleman Regency in conjunction with other stunting reduction programs. Methods: This study was a qualitative study with a case study approach. Data collection techniques included document analysis, 4 sessions of focus group discussions, in-depth interviews involving 11 key informants, and reflective journals. Data were analyzed using thematic analysis method. Results: In 2022, there were 34 Family Quality Village in the Sleman Regency. We obtained 3 major themes; program acceptance among stakeholders, synergy with other stunting related programs, and program management. Several local government agencies and community health staff working on stunting reduction efforts were not familiar with the concept of the Family Quality Village Program, thus affecting stakeholder acceptance and synergies with other stunting programs. Additionally, this program experienced significant changes regarding the local governance system which required adjustment in the program management, hence affecting the program effectiveness. Conclusions: It is crucial to increase awareness of the program and coordination to ensure its optimum impact on stunting reduction efforts. The local governance system should also be considered to ensure program acceptance among stakeholders.